Pulmonary Rehabilitation - Charususin, Noppawan (Journal of Health Science of Thailand, 2017)
The number of patients with chronic pulmonary disease, especially chronic obstructive pulmonary disease (COPD) is increasing. One major problem is the increase of recurrent episodes which leads to patient re-admission. Patients who receive a suitable pulmonary rehabilitation program can control and alleviate the symptoms such as dyspnea, as well as improve the quality of life and lengthen survival for patients. Key components of pulmonary rehabilitation programs consist of the assessment, exercises to improve general strength, endurance, muscle flexibility, exercises to improve respiratory muscle function, ventilator therapy, psychological and behavioral management, and patient and family education. Designing a rehabilitation program needs to be integrated for promoting patients’ quality of life.